Application of Environmental Care Character Values for Class XI Students at SMAN 13 Surabaya - Panggestu, Ibnu Graha Ade; Suhari, Suhari (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
Human disregard for the environment leads to environmental issues that exacerbate natural disasters. One of the most crucial elements in developing good character in pupils is their lack of recognizing the requirement of defending the environment. In order for nation"™s future country, especially the students of SMAN 13 Surabaya, to be good citizens and people of character, they must learn the importance of protecting the environment. Descriptive qualitative research is being conducted to find out how environmentally caring character values are taught to students, how teachers can help students develop these values, and what supports and prevents the application of environmentally caring character values at SMAN 13 Surabaya. Study participants were SMAN 13 Surabaya instructors and students. gathering information through documentation, interviews, and observation. The outcomes proved that the character values of environmental care were successfully implemented for grade XI students at SMAN 13 Surabaya. It is obvious in the ways that it grows in accordance with signs, such as students bringing water bottles from home, riding motorcycles in the morning, and putting trash in the proper location. The teacher's job is to provide an example, instill habits, and provide direction. The involvement of school personnel, the infrastructure and facilities, and the environmental activities' habituation are the supporting aspects. The impact of student living and the lack of time for maintaining the environment are the barriers.